Deciphering cleaner and sustainable frontiers in scientific cow waste valorization: a review - Kushwaha J.; Singh Y.; Yadav S.K.; Sheth P.N.; Mahesh M.S.; Dhoble A.S. (My University, 2025)
The forecasted global population growth is poised to create a greater exigency for livestock-derived food production, leading to a significant waste generation from the industrial-scale livestock operations, which necessitates to develop sustainable waste management solutions. The heightened demand for livestock and dairy products has driven a surge in cow waste (CW) production. While CW is typically used as organic fertilizer or solid fuel, improper disposal poses potential environmental hazards. Anaerobic digestion and composting transform CW into valuable products, such as biofuels and organic fertilizers, with the potential for electricity and heat generation, biochar production, and advanced friction materials. The CW contains essential inorganic and organic compounds vital for plant functions, including lignin, cellulose, hemicellulose, nitrogen, and minerals such as potassium, sulfur, iron, magnesium, copper, cobalt, and manganese. Additionally, the rich microbial diversity in cow dung drives the production of bioenergy carriers like biomethane and biohydrogen, promoting cost-effective energy generation and environmental sustainability. This review employs bibliometric analysis to explore the latest trends in CW applications, with a particular focus on innovative applications such as cellulose extraction, biochar production, microbial fuel cells, and nanoparticle synthesis. It further evaluates the environmental impacts of these technologies and assesses their potential to advance sustainable and cleaner frontiers in the valorization of CW. Graphical Abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.